2022
DOI: 10.3390/cells11121927
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Pathogenomic Insights of Breast Cancer in Young Women

Abstract: The prognosis of breast cancer (BC) in young women (BCYW) aged ≤40 years tends to be poorer than that in older patients due to aggressive phenotypes, late diagnosis, distinct biologic, and poorly understood genomic features of BCYW. Considering the estimated predisposition of only approximately 15% of the BC population to BC-promoting genes, the underlying reasons for an increased occurrence of BCYW, at large, cannot be completely explained based on general risk factors for BC. This underscores the need for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…While other tryptic peptides such as m/z 1550.809 from the collagen α2(I) chain and m/z 1797.841 from the collagen α1(III) chain were localized primarily to regions outside the DCIS and IDC lesions ( Figure 6 H and Figure S9 ). In contemporary literature, a transcriptional signature including COL1A2 was associated with reduced overall survival in breast cancer [ 41 ]. Similarly, COL3A1 has been reported to have an important role in breast cancer progression as knockdown studies in triple-negative breast cancer cell lines have been linked to reduced invasion and proliferation [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…While other tryptic peptides such as m/z 1550.809 from the collagen α2(I) chain and m/z 1797.841 from the collagen α1(III) chain were localized primarily to regions outside the DCIS and IDC lesions ( Figure 6 H and Figure S9 ). In contemporary literature, a transcriptional signature including COL1A2 was associated with reduced overall survival in breast cancer [ 41 ]. Similarly, COL3A1 has been reported to have an important role in breast cancer progression as knockdown studies in triple-negative breast cancer cell lines have been linked to reduced invasion and proliferation [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that age-related differences reside at the molecular level or by gene expression [ 23 ]. A recent study based on breast cancer genomic datasets revealed a dysregulation of age-associated cancer-relevant gene sets in both cancer and normal breast tissues, and sub-sets of which adversely affect the survival in young women with breast cancer [ 24 ]. Further studies are warranted to identify a biological or molecular explanation for the higher relapse rate of breast cancer in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although less studied in breast cancer compared to COL1A1, COL1A2 is identified as a hub gene associated with the survival outcomes of human epidermal growth factor receptor 2 (HER2)-positive patients by constructing the protein–protein interaction (PPI) network. 54 Upregulated in breast cancer tissues, COL1A2 is correlated with reduced overall and recurrence-free survival, 55 and its expression is elevated by radiation. 28 Research on its mechanism in breast cancer is ongoing, with previous studies indicating potent induction of COL1A2 transcription by TGF-β, involving Smad family proteins or Smad-binding elements.…”
Section: Collagen Type I Alpha 2 Chain (Col1a2)mentioning
confidence: 99%